Anxiety and Family Support on Infected TORCH Patients - Eirene Shinta Valevi; Lina Handayani (International Journal of Public Health Science (IJPHS), 2014)
TORCH is an acronym of Toxoplasmosis, Rubella, Cytomegalovirus, and Herpes simplex diseases. These diseases can cause abnormalities in the brain, impaired psychomotor and cognitive function, fertility, miscarriage, birth defects, etc. Infected TORCH patient tend to experience anxiety and worry after discovering he/she was diagnosed infected TORCH. For infected TORCH patient, family support is external factors that influence the treatment TORCH process. The purpose of this study was to describe the anxiety and family support on infected TORC patients in Klinik Utama Thursina Husada,Yogyakarta, Indonesia. The design of this study was descriptive qualitative with case study approach. All subjects in this study had worries on costly medical expenses TORCH. TORCH symptoms that asymptomatic made informants and family ever thought that it was a non-medical disease. Each informant can overcome the anxiety that they face because of emotional support, esteem support, instrumental support, and informational support from family. Infected TORCH caused the patient had anxiety and worries. Family support was very helpful in the process of TORCH treatment.